Survival of trawl-caught fish in experimentalfishing in the Gulf of Mannar and Palk Bay offsoutheast coast of India - Jayasankar, P (Indian Journal of Fisheries, 2011)
Survival of injured fish caught in a series of experimental trawl hauls conductedin the Gulf of Mannar and Palk Bay (8°55’ – 9°20’N; 79° - 79°40’E) in the southeastcoast of India has been examined. Larger size groups of trawl-caught finfishsurvived longer, while inedible organisms showed shorter duration of survival.Among the target groups, the blue crab, Portunus pelagicus had the greatestsurvival ratio. Among the non-target groups, molluscs and stomatopods survivedbetter than others. Generally, inedible taxa were relatively more resilient totrawling pressures, showing better survival and reduced injury.